2019
DOI: 10.1177/1464884919868325
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of disinformation: How social media users respond to fake news and why

Abstract: This exploratory study seeks to understand the diffusion of disinformation by examining how social media users respond to fake news and why. Using a mixed-methods approach in an explanatory-sequential design, this study combines results from a national survey involving 2501 respondents with a series of in-depth interviews with 20 participants from the small but economically and technologically advanced nation of Singapore. This study finds that most social media users in Singapore just ignore the fake news pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(179 citation statements)
references
References 38 publications
10
163
0
6
Order By: Relevance
“…A survey of 2501 respondents from Singapore found that most social media users simply ignore “fake news” posts they come across on social media, only offering corrections when the issue is strongly relevant to them and to people with whom they share a strong personal relationship [82] . An active call for intervention is potentially useful because it would allow researchers to frame the COVID-19 infodemic as something strongly relevant to media consumers, which in turn could allow organic checks on misinformation.…”
Section: Discussion and Implications For Future Workmentioning
confidence: 99%
“…A survey of 2501 respondents from Singapore found that most social media users simply ignore “fake news” posts they come across on social media, only offering corrections when the issue is strongly relevant to them and to people with whom they share a strong personal relationship [82] . An active call for intervention is potentially useful because it would allow researchers to frame the COVID-19 infodemic as something strongly relevant to media consumers, which in turn could allow organic checks on misinformation.…”
Section: Discussion and Implications For Future Workmentioning
confidence: 99%
“…Given these competing explanations, it is unclear, then, whether seeing corrections will increase or decrease the likelihood of responding. Given the lack of research on prompting user response to misinformation (see Tandoc et al, 2020 for an exception) and competing explanations for what exposure to other corrections may prompt, we ask, Because research suggests that observational correction reduces misperceptions (e.g., Margolin et al, 2018;, we expect that exposure to corrections will increase the likelihood that participants will reply to the misinformation with correct information (compared to exposure to misinformation only). Moreover, in this study, the second correction adds additional information about the safety of raw milk, noting that pasteurization kills potentially dangerous bacteria in raw milk, offering new information that may encourage users to reply in support of this claim, which is not addressed in the original misinformation post.…”
Section: Responding To Misinformation On Social Mediamentioning
confidence: 99%
“…Due to the private and intimate nature of these services, corrections on MIMS are instead more likely to occur between users who know each other. Scholarly work on social media and misinformation does find that people are more motivated to correct close friends and family members than strangers (Tandoc et al, 2019). Furthermore, a correction coming from a known other is more readily accepted than a correction from a stranger (Margolin et al, 2018).…”
Section: Relational Correctionmentioning
confidence: 99%